The Effect of IAA and BAP on Root Induction of Cattleya Orchids - Harahap, Fauziyah; Sinuraya, Kenari Br; Syarifuddin, Syarifuddin; Suriani, Cicik; Ningsih, Ayu Putri; Edi, Syahmi; Nusyirwan, Nusyirwan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Orchid is an ornamental plant commodity that has an important meaning in international trade. Until now, orchids are still the center of attention of farmers and lovers of ornamental plants, because of their bright potential as cut flowers and potted plants. The popular and widespread type of orchid is Cattleya sp. The Cattleya orchid is also called the queen of orchids because of its colorful flowers. Cattleya sp. orchids take a long time to propagate by seed, about 4 to 7 years, so other methods are needed to deal with them. Tissue culture is a method for isolating plant parts such as cells, tissues or organs, and cultivating them in an aseptic environment. The purpose of this study was to determine the optimal interaction of growth regulators indole acetic acid (IAA), benzyl amino purine (BAP), and their interactions with the root induction of Cattleya sp. Cytokinins interact with auxin in determining the direction of cell differentiation. In this research method, differences in concentrations of indole acetic acid (IAA: 0, 2, 4, 6 ppm) and concentrations of benzyl amino purine (BAP: 0, 0, 5, 1 ppm) were carried out. Parameters observed were the number of roots and root length. Data were analyzed descriptively and inferentially using ANOVA. The highest number of roots was obtained in the treatment medium containing 0.5 ppm BAP and 6 ppm IAA, which was 6.33. The highest root length was found in the B0I4 treatment (BAP 0 + IAA 4 ppm). The results of the analysis of the interaction variance between the IAA treatment and the BAP treatment were 0.005, meaning that there was a significant effect of the combination of IAA and BAP on the leaf length of Cattleya sp.